Strangulated Incisional Hernia Post Appendectomy: A Rare Case Report - Rahayu, Dewi; Hendwell; Hendsun; Bermana, Frengky (HM Publisher, 2024)
Background: Incisional hernia is a condition in which internal organs, such as the intestines, protrude through a previous surgical incision or suture. This occurs due to the failure of the abdominal wall to close properly. The closure of the abdominal wall is influenced by patient-related factors and technical factors during surgery. Incisional hernia following appendectomy is a rare condition, with an incidence rate of less than 0.12%. With this case report, the author aims to contribute to the literature on strangulated incisional hernia post-appendectomy. Case presentation: A 42-year-old male presented to the emergency department with complaints of right lower abdominal pain for the past three days. The patient reported a lump that had been intermittently present for the past nine years but became persistent three days ago. The patient had a history of appendectomy nine years ago. Vital signs were relatively stable, and physical examination revealed a bluish mass measuring 10x8x4 cm in the abdomen. Radiological abdominal assessment revealed a high-level obstructive ileus. Subsequently, the patient underwent a laparotomy, and a right hemicolectomy was performed, removing a segment measuring 50 cm from the ileocecal junction to the ascending colon. Conclusion: Incisional hernia following appendectomy is a rare complication, but it can occur due to various risk factors, such as surgical site infection, improper choice of suture material, and inappropriate wound closure technique. The management of this condition can involve the use of tension-free synthetic mesh in either laparotomy or laparoscopy.